2021
DOI: 10.33785/ijds.2021.v74i02.010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and adoption level of dairy farmers about bovine ectoparasites in the operational area of dairy Vigyan Kendra, Vejalpur, Gujarat (India)

Abstract: The study was carried out to assess the knowledge and adoption level of dairy farmers about bovine ectoparasites in the operational area of Dairy Vigyan Kendra (DVK), Vejalpur, Gujarat (India) during 2019-2020. Using the simple random sampling method, 300 respondents from 30 villages of 10 talukas in the operational area of Dairy Vigyan Kendra, Vejalpur were selected. Majority of dairy farmers (80.33%) reported that their animals were suffering from ticks. An interview schedule was prepared encompassing variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The majority (81.50%) of dairy owners reported that tick problem infestation is more during summer and rainy season followed by 13.50 percent who had observed throughout the year. Five percent farmers reported tick infestation in their animals in summer, rainy & autumn season (Table 1 The farmers rely on the knowledge of veterinarians to control ectoparasites (Jadav et al 2021). The effect of synthetic acaricides was short-lived as the majority (79.5 %) of the farmers reported a re-occurrence of infestation within 30 days of application.…”
mentioning
confidence: 99%
“…The majority (81.50%) of dairy owners reported that tick problem infestation is more during summer and rainy season followed by 13.50 percent who had observed throughout the year. Five percent farmers reported tick infestation in their animals in summer, rainy & autumn season (Table 1 The farmers rely on the knowledge of veterinarians to control ectoparasites (Jadav et al 2021). The effect of synthetic acaricides was short-lived as the majority (79.5 %) of the farmers reported a re-occurrence of infestation within 30 days of application.…”
mentioning
confidence: 99%